2001
DOI: 10.2134/jeq2001.3041271x
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Degradation of Atrazine and Metolachlor and Metabolite Formation in Wetland Soil and Water Microcosms

Abstract: The half-lives, degradation rates, and metabolite formation patterns of atrazine (6-chloro-N2-ethyl-N4-isopropyl-1,3,5-triazine-2,4-diamine) and metolachlor [2-chloro-N-(2-ethyl-6-methylphenyl)-N-(2-methoxy-1-methylethyl) acetamide] were determined in an anaerobic wetland soil incubated at 24 degrees C for 112 d. At 0, 7, 14, 28, 42, 56, and 112 d, the soil and water were analyzed for atrazine and metolachlor, and their major metabolites. The soil oxidation-reduction potential reached -200 mV after 14 d. Degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 41 publications
4
26
0
1
Order By: Relevance
“…Although the DAR concept is typically used to distinguish groundwater sources from runoff water sources in stream water, processing of ground water through an anaerobic, high-organic matter (OM) wetland soil (and subsequent removal of CIAT) will alter the signal. Kruger et al (15) reported that anaerobic processes were more active at removing atrazine and atrazine metabolites than were aerobic processes; Seybold et al (16) also noted high atrazine degradation in anaerobic soil. High DAR values in oxic ground water, then, can diminish as ground water moves up through anoxic soil (Figure 6), as the degradate (CIAT) is consumed or adsorbed in that environment.…”
Section: Resultsmentioning
confidence: 99%
“…Although the DAR concept is typically used to distinguish groundwater sources from runoff water sources in stream water, processing of ground water through an anaerobic, high-organic matter (OM) wetland soil (and subsequent removal of CIAT) will alter the signal. Kruger et al (15) reported that anaerobic processes were more active at removing atrazine and atrazine metabolites than were aerobic processes; Seybold et al (16) also noted high atrazine degradation in anaerobic soil. High DAR values in oxic ground water, then, can diminish as ground water moves up through anoxic soil (Figure 6), as the degradate (CIAT) is consumed or adsorbed in that environment.…”
Section: Resultsmentioning
confidence: 99%
“…Anaerobic biodegradation of atrazine has been shown to occur in soil, wetland, and wastewater samples. [8][9][10][11][12] However, in aquifers atrazine and metabolites can persist for decades or even longer. [13][14][15] The known biochemical steps of atrazine biodegradation are hydrolytic and do not require molecular O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Glucose is a much more soluble compound than the three herbicides and a poor competitor for adsorption sites. Also, it appears unlikely that microbial degradation of any of the herbicides was greatly affected by the incubation with glucose; Seybold et al [23] have shown losses of less than 5% of freshly added atrazine or metolachlor during 7 days incubation at 24°C. Here anaerobiosis was achieved in 5 2 days and then microbial activity was inhibited by the addition of methanol (20%).…”
Section: Resultsmentioning
confidence: 99%